Proliferative activity of urothelial neoplasms: comparison of BrdU incorporation, Ki67 expression, and nucleolar organiser regions. Issue 2 (February 1993) - Limas, C; Bigler, A; Bair, R; Bernhart, P; Reddy, P
Abstract : AIMS: To evaluate the proliferative activity of urothelial neoplasms, compare it with that of the normal urinary tract epithelium, and determine its relation to morphological grade and presence of invasion. METHODS: Multiple biopsy specimens from 53 individuals--eight normal controls, five patients with severe urothelial atypia, and 40 with transitional cell carcinomas (TCCs)--were studied using in vitro bromodeoxyuridine (BrdU) incorporation, Ki67 antigen expression, and quantitation of the nucleolar organiser regions (NORs). RESULTS: The percentage of nuclei labelled by BrdU (BrdU index) correlated well with the percentage of nuclei expressing the Ki67 antigen (Ki67 index). These proliferation indices were very low (less than 0.1% in 60% of samples) in the urothelium of normal controls and the morphologically unremarkable epithelium of patients with TCCs. Non-invasive TCCs had increased proliferation (BrdU index 6.32 (SD 0.8)%, Ki67 index 5.04 (0.6)% but lagged behind the invasive tumours (BrdU 20.9 (3.2)%, Ki67 18.6 (2.8)%). The average NOR count was 1.57 (0.03) in morphological normal epithelium, which increased progressively with grade in non-invasive TCCs, but varied greatly in invasive tumours and did not correlate with the proliferation indices. The spectrum of values for both proliferation indices and NORs was particularly wide in grade 2 TCCs. Severe atypias without exophytic growth had an increase in BrdU and Ki67 indices comparable with that found in grade 3-4 invasive TCCs; these also had the highest NORs per nucleus. CONCLUSIONS: The growth potential of urothelial neoplasms is an important indicator of their aggressive course. In particular, growth indices over 10% are strongly associated with the presence of invasion. Papillary grade 2 TCCs show heterogeneity in their growth characteristics which may relate to their diverse clinical course. The mitotic count underestimates the growth potential of papillary TCCs and the addition of proliferation indices such as BrdU incorporation or the Ki67 index may enhance the prognostic accuracy of conventional morphological grading.